DIGITAL RADICALISM: IDEOLOGICAL SECURITY CHALLENGES IN THE SOCIAL MEDIA ERA - Muhammad Abrar Mansyur; Raditya Al Fath; Kurniati Kurniati (PT. Altin Riset Publishing, 2026)
Digital transformation has brought fundamental changes to various aspects of social, political, and religious life. The rapid development of social media and online platforms has not only expanded public participation but has also generated new challenges in the form of the dissemination of extremist ideologies, commonly referred to as digital radicalism. Digital radicalism refers to the spread of radical and extremist ideas through social media that occurs rapidly, massively, and is difficult to control. This phenomenon poses not only a threat to national security but also a serious challenge to ideological security, particularly to the values of Pancasila, pluralism, tolerance, and democracy in Indonesia. This article aims to comprehensively examine the phenomenon of digital radicalism, including its driving factors, the role of social media in the process of radicalization, and its implications for ideological security. The research employs a qualitative descriptive approach through a literature review by analyzing 30 scholarly references consisting of academic books, research reports, and relevant national and international journal articles. The findings indicate that digital radicalism develops as a result of a combination of ideological, social, political, and technological factors, reinforced by low levels of digital literacy and ideological awareness within society. Social media plays a significant role in accelerating the radicalization process through algorithmic mechanisms and information echo chambers. Therefore, strengthening Pancasila-based ideological education, enhancing digital literacy, promoting religious moderation, and revitalizing local wisdom are essential and sustainable strategies to address the challenges of digital radicalism in the era of social media.